A degradable lunch box and preparation method thereof
By using biodegradable coatings made of biodegradable materials such as polylactic acid in the lunch box, and by modifying modified hemp fiber and tapioca starch, the problem of poor combination stability of environmentally friendly coating materials in high temperature environments is solved, and the temperature resistance performance of the lunch box is improved and the application quality is optimized.
Patent Information
- Application Number
- CN202411122667.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-15
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-08-15
AI Technical Summary
The bonding stability between existing environmentally friendly coating materials and paper substrates in high temperature environments is poor, resulting in poor lunch box application experience.
The degradable coating consisting of polylactic acid, polybutylene succinate, polyglycolic acid, tapioca starch, modified hemp fiber, montmorillonite and boron nitride nanotubes is used to improve the thermal stability and adhesion properties of the coating through the modification of modified hemp fiber and tapioca starch.
It significantly improves the temperature resistance of the biodegradable lunch box, ensures a stable combination between the coating and the paper lunch box substrate, and improves the application quality of the lunch box.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of degradable packaging, and more specifically, to a degradable lunch box and a preparation method thereof. Background Art
[0002] A lunch box is a convenient and quick container for holding food, commonly seen in takeout, picnics, office dining and other scenarios; a paper lunch box refers to a lunch box made of paper material, usually made of pulp, which is very environmentally friendly and degradable. It is generally a disposable paper lunch box, which is easy to use, low cost, and has been widely used in the catering industry.
[0003] However, the use of paper lunch boxes also has its limitations. For example, they are not suitable for loading liquid food and have poor waterproof and oil-proof properties. Therefore, a thin coating is applied on the surface of the paper lunch boxes to make them waterproof, oil-proof and high-temperature resistant. Currently, the coating on the surface of paper lunch boxes is usually synthetic plastic. As a non-natural petroleum-based plastic, although it can withstand high temperatures and is waterproof and oil-proof, it has no problems in packaging food and handling cold and hot drinks. However, plastic monomers are often bonded by very strong covalent bonds such as CC bonds. It is very difficult to destroy this polymer chain, and the microbial degradation process and efficiency are extremely slow. Therefore, these polymers are difficult to be degraded by microorganisms after entering the environment.
[0004] With the continuous strengthening of environmental awareness, more and more companies have begun to develop environmentally friendly coating materials, among which oil-proof paper water-based biodegradable coating is a representative environmentally friendly coating material. Oil-proof paper water-based biodegradable coating is made of one or more bio-based materials processed by appropriate methods, and its main components are biodegradable materials such as starch and polylactic acid. The coating can be evenly and firmly attached to the surface of substrates such as paper and cardboard, and can form a waterproof and oil-proof coating on the surface of substrates such as paper and cardboard. The advantages are that environmentally friendly, degradable and biodegradable substances have little impact on the environment, and the preparation cost is low.
[0005] Regarding the above-mentioned related technologies, the inventors believe that although the above-mentioned environmentally friendly coating materials have the advantages of being waterproof, oil-proof, environmentally friendly, and biodegradable, their overall temperature resistance is poor. During the process of cooling down hot food in the lunch box and heating the lunch box together with the food, it is difficult to maintain a stable bond between the environmentally friendly coating material and the paper substrate, and debonding is likely to occur, which in turn leads to a poor application experience of the lunch box.
[0006] Therefore, it is urgent to propose a solution to solve the above technical problems. Summary of the invention
[0007] In order to improve the temperature change resistance of the environmentally friendly coating material, maintain a stable combination with the paper substrate, and further improve the application quality of the lunch box, the present application provides a degradable lunch box and a preparation method thereof.
[0008] In the first aspect, the present application provides a degradable lunch box, which adopts the following technical solution:
[0009] A degradable lunch box, comprising a paper lunch box substrate and a degradable coating disposed on the paper lunch box substrate, wherein the degradable coating is made of raw materials comprising the following parts by weight:
[0010] Polylactic acid 40-50 parts;
[0011] 10-15 parts of polybutylene succinate;
[0012] Polyglycolic acid 15-20 parts;
[0013] 10-20 parts of tapioca starch;
[0014] 5-8 parts of external additives;
[0015] Montmorillonite 1.2-1.8 parts;
[0016] Boron nitride nanotubes 0.2-0.8 parts;
[0017] 1.5-2.5 parts of modified hemp fiber;
[0018] The modified hemp fiber is prepared by the following modification steps:
[0019] S1, taking the hemp fiber raw material at a weight ratio of 1: (25-35) and immersing it in deionized water, and adding 0.8-1.5% by weight of silane coupling agent into the deionized water, immersing for 20-30 minutes, taking it out and drying it to obtain pretreated hemp fiber;
[0020] S2. Take N-acetoacetanilide, propylene glycol and potassium tert-butoxide in a molar ratio of 1: (1.1-1.3): (0.9-1.1) and stir to react in DFM solvent. After the reaction, pour into saturated sodium chloride solution. Prepare the precipitated solid into 8-12% ethanol solution. Finally, immerse the pretreated hemp fiber in the prepared solution at a weight ratio of 1: (18-20). After immersion for 4-6 hours, take out, wash and dry to obtain modified hemp fiber.
[0021] By adopting the above technical scheme, polylactic acid is made from lactic acid as raw material, and traditional lactic acid fermentation mostly uses starch raw materials; polybutylene succinate is formed by condensation polymerization of succinic acid and 1,4-butanediol, and the raw material source is petroleum or biological resource fermentation; polyglycolic acid is a thermoplastic linear polyglycolic acid with good biodegradability and biocompatibility; cassava starch not only has excellent biodegradability, but also contains a large amount of branched starch, so that cassava starch can provide stable viscosity for the combination of various component raw materials after dispersion; polylactic acid, polybutylene succinate, polyglycolic acid and cassava starch are combined to obtain a stable and degradable matrix, and when other raw materials are introduced, they can form a stable combination with each other and exert excellent corresponding effects.
[0022] Hemp fiber can be quickly degraded into harmless substances in the natural environment and is a natural environmentally friendly material. Modification of hemp fiber can not only improve the interfacial adhesion of hemp fiber, but also improve the thermal stability of hemp fiber. Boron nitride nanotubes can not only improve the structural toughness of the degradable coating, but also have rapid heat conduction capabilities. Montmorillonite acts as a physical cross-linking point in the degradable coating, which can inhibit the movement of molecular chains to a certain extent, thereby improving thermal stability. When montmorillonite, boron nitride nanotubes and modified hemp fiber are used in combination, they can bring excellent The combination effect is that part of the boron nitride nanotubes and montmorillonite are accommodated in the hollow structure of the modified hemp fiber to form a stable gradient heat conduction path, and use their own capillary action to take root in the paper lunch box matrix. When subjected to temperature changes brought about by the external environment, the combination of montmorillonite, boron nitride nanotubes and modified hemp fibers can greatly avoid structural damage to the degradable coating caused by thermal stress changes, and maintain a relatively stable combination between the degradable coating and the paper lunch box matrix, thereby making the degradable lunch box exhibit excellent temperature change resistance and have significantly excellent application quality.
[0023] Preferably, the weight ratio of the montmorillonite, the boron nitride nanotubes and the modified hemp fiber is 1.5:0.5:2.
[0024] By adopting the above technical scheme, when the montmorillonite, boron nitride nanotubes and modified hemp fibers in the above weight ratio are used, each raw material can not only stably exert its own function, but also can partially combine to form a stable combination, and the combination of montmorillonite, boron nitride nanotubes and modified hemp fibers can be evenly dispersed and fully volatilized in the degradable coating, thereby bringing an excellent and stable compound effect, so that the temperature change resistance of the degradable lunch box is better and the overall quality is also better.
[0025] Preferably, the particle size of the montmorillonite is 50-100 nm; the diameter of the boron nitride nanotubes is 45-55 nm, the length is 10-20 μm, and the specific surface area is 40-50 m 2 / g; the single fiber fineness of the modified hemp fiber is 15-30μm.
[0026] By adopting the above technical scheme, when the montmorillonite, boron nitride nanotubes and modified hemp fibers of the above specifications are used in combination, more combinations of montmorillonite, boron nitride nanotubes and modified hemp fibers are formed, and they are evenly dispersed in the degradable coating to exert better temperature change resistance; at the same time, in the hollow structure of the modified hemp fiber, a more uniform and clear staggered distribution structure of boron nitride nanotubes with montmorillonite as the staggered connection point is formed, which brings about a better gradient thermal conductivity path effect, and the bonding stability maintained with the modified hemp fiber and the paper lunch box substrate is also better, so that the combination between the degradable coating and the paper lunch box substrate shows excellent temperature change resistance, and the application quality of the degradable lunch box is better.
[0027] Preferably, the cassava starch is modified before use, and the modification steps are as follows:
[0028] Take cassava starch and deionized water in a ratio of 1g: (8-10) ml, mix them, heat them to 90-95°C, add cellulose, keep them at a constant temperature for 8-10 minutes, cool them to 35-40°C, add calcium carbonate and polyvinyl alcohol, stir and mix, and finally roll and knead them, then cut them into pieces and pelletize them to obtain modified cassava starch;
[0029] In the above operation, the weight ratio of cassava starch, cellulose, calcium carbonate and polyvinyl alcohol is (4.5-6): (3.5-4): (2-3): 1.
[0030] By adopting the above technical scheme, calcium carbonate can improve the stability of the modified cassava starch mixed system; cellulose has strong mechanical strength and chemical stability, and acts as a skeleton in the modified cassava starch mixed system; polyvinyl alcohol can significantly improve the viscosity and heat resistance of the modified cassava starch mixed system; and the use of cellulose, calcium carbonate and polyvinyl alcohol in combination to modify the cassava starch greatly improves the compatibility of the modified cassava starch with other component raw materials, and to a certain extent improves the bonding stability between the degradable coating and the paper lunch box matrix. At the same time, the affinity and bonding between the modified cassava starch and the modified hemp fiber are more prominent, making it easier to stably exert the corresponding effects brought about by the compounding of montmorillonite, boron nitride nanotubes and modified hemp fibers, thereby further improving the temperature change resistance of the degradable lunch box and further improving the overall application quality.
[0031] Preferably, the weight ratio of cassava starch, cellulose, calcium carbonate and polyvinyl alcohol is 5.5:3.5:2.5:1.
[0032] By adopting the above technical scheme, the modified cassava starch prepared by using cassava starch, cellulose, calcium carbonate and polyvinyl alcohol in the above usage ratio can be closely combined with other component raw materials and fully play their role during the actual application process, thereby also having a better improvement effect on the temperature change resistance of the degradable lunch box, and the overall application quality of the degradable lunch box is also better.
[0033] Preferably, the external additive is one or a combination of fillers, thickeners and antibacterial and antifungal agents.
[0034] By adopting the above technical scheme, the filler can improve the dimensional stability and surface smoothness of the degradable coating, and different fillers can also improve the overall performance of the degradable coating according to their own characteristics; the thickener can increase the viscosity and consistency of the substance, thereby improving the texture, stability and use experience of the product; the antibacterial and mildew-proof agent can inhibit or kill the growth of bacteria and mold through the dispersion effect of the antibacterial ion antibacterial additive powder, thereby extending the service life of the degradable coating; and the above raw materials can be used as external additives, and can be evenly dispersed with other component raw materials to form a stable mixed state, and can play an excellent role themselves.
[0035] Preferably, the filler is one or a combination of talc powder, silica powder, mica powder, silicon whisker, calcium whisker, glass fiber, titanium dioxide and glass microspheres.
[0036] Preferably, the thickener is one or a combination of sodium carboxymethyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl cellulose, sodium alginate and polyacrylamide.
[0037] Preferably, the antibacterial and antifungal agent is polyhexamethyleneguanidine hydrochloride.
[0038] By adopting the above technical solution, the above-mentioned types of fillers, thickeners and antibacterial and antifungal agents can be stably dispersed among the other component raw materials and can fully play their own roles in the mixed system of the degradable coating. At the same time, according to the actual application scenarios of the degradable lunch box, multiple combinations can be selected to further improve the product diversity of the degradable lunch box.
[0039] In a second aspect, the present application provides a method for preparing a degradable lunch box, using the following technical solution:
[0040] A method for preparing a degradable lunch box comprises the following steps:
[0041] (1) preparing raw materials including polylactic acid, polybutylene succinate, polyglycolic acid, cassava starch, external additives, montmorillonite, boron nitride nanotubes and modified hemp fiber according to a ratio;
[0042] (2) heating the polylactic acid, polybutylene succinate and polyglycolic acid in step (1) to a molten state and mixing them uniformly, then adding cassava starch and external additives and mixing them, and finally adding montmorillonite, boron nitride nanotubes and modified hemp fibers and mixing them, and extruding and granulating them to obtain biodegradable coated particles;
[0043] (3) feeding the paper lunch box substrate into a laminating machine, and melting the degradable coating particles and laminating them on the surface of the paper lunch box substrate, and forming a degradable coating after cooling to obtain a coated paper;
[0044] (4) After the coated paper is cut and formed into a box, a degradable lunch box is obtained.
[0045] By adopting the above technical scheme, the above preparation method is simple to operate, and each raw material is added and used in steps, which is convenient for quality control in the process, and is conducive to obtaining a degradable lunch box with stable and excellent quality, which is suitable for large-scale industrial production. At the same time, in the preparation of degradable coating particles, polylactic acid, polybutylene succinate, and polyglycolic acid are first heated and melted and mixed, and then cassava starch and external additives are added, which is conducive to obtaining a uniform and stable degradable matrix, and then montmorillonite, boron nitride nanotubes and modified hemp fibers are added, so that the three raw materials are fully dispersed and play their own roles, and can also be partially combined with each other to play an excellent compounding effect, ensuring that the degradable coating and the paper lunch box matrix can be stably combined in a temperature change environment, thereby helping to obtain a degradable lunch box with excellent temperature change resistance.
[0046] In summary, this application has the following beneficial effects:
[0047] 1. The present application modifies hemp fiber and uses montmorillonite, boron nitride nanotubes and modified hemp fiber in combination. The combination formed by part of montmorillonite, boron nitride nanotubes and modified hemp fiber can greatly avoid the structural damage of the degradable coating due to thermal stress changes, and maintain a relatively stable combination between the degradable coating and the paper lunch box substrate, thereby making the degradable lunch box show excellent temperature change resistance;
[0048] 2. The present application uses a combination of cellulose, calcium carbonate and polyvinyl alcohol to modify cassava starch, and utilizes the high affinity and binding property between modified cassava starch and modified hemp fiber to make it easier to stably exert the corresponding effects brought about by the compound of montmorillonite, boron nitride nanotubes and modified hemp fiber, and can further improve the bonding stability between the degradable coating and the paper lunch box matrix, so that the temperature change resistance of the degradable lunch box is further improved, and the overall application quality is better. DETAILED DESCRIPTION
[0049] The present application is further described in detail below in combination with preparation examples, embodiments and comparative examples.
[0050] Unless otherwise specified, the raw materials used in the preparation examples and embodiments of the present application are commercially available:
[0051] Polylactic acid was purchased from Dongguan Hesheng Plastic Co., Ltd., model number Fengyuan FY201;
[0052] Polybutylene succinate was purchased from Shanghai Yilun Plastics Co., Ltd., model number PBATecoflex C1200;
[0053] Polyglycolic acid was purchased from Wuhan Shuer Biotechnology Co., Ltd., model number XH6240MOKQ05;
[0054] Cassava starch was purchased from Dongying Huaxuan Biotechnology Co., Ltd., model hx-05;
[0055] Montmorillonite was purchased from Jinfan Mineral Products Processing Plant in Lingshou County, coating industrial grade;
[0056] Boron nitride nanotubes were purchased from Zhongke Leiming (Beijing) Technology Co., Ltd., model BNNT-50;
[0057] Hemp fiber was purchased from Tongxiang Shangde Textile Co., Ltd. bleached hemp fiber;
[0058] Cellulose was purchased from Yuanda Mica Factory, Lingshou County, model number Yuanda Mining 01-2011;
[0059] Calcium carbonate was purchased from Yongshun Mineral Products Processing Plant in Lingshou County, and the specification was 800-mesh light calcium carbonate;
[0060] Polyvinyl alcohol was purchased from Shandong Yueyang New Materials Co., Ltd., model PVA20-99;
[0061] The paper lunch box substrate was purchased from Russian white kraft paper from Dongguan Jiali Industrial Investment Co., Ltd., with a thickness of 0.35 mm;
[0062] Talc powder was purchased from Lingshou County Yehui Mineral Products Co., Ltd., industrial grade, specification 325 mesh;
[0063] Hydroxyethyl cellulose was Clariant Cellulose, model HS30000;
[0064] Polyhexamethyleneguanidine hydrochloride was purchased from Shandong Poly Chemical Co., Ltd. with a CAS number of 57028-96-3.
[0065] Preparation examples of raw materials and / or intermediates
[0066] Preparation Example 1
[0067] A modified hemp fiber is prepared by the following modification steps:
[0068] S1, taking the hemp fiber raw material at a weight ratio of 1:30 and immersing it in deionized water, and adding 1.2% by weight of silane coupling agent into the deionized water, after immersion treatment for 25 minutes, taking it out and drying it to obtain pretreated hemp fiber;
[0069] S2, take N-acetoacetanilide, propylene glycol and potassium tert-butoxide in a molar ratio of 1:1.2:1 in 4 times the mass of DFM solvent, stir and react for 4 hours, pour into saturated sodium chloride solution after the reaction, prepare 10% concentration ethanol solution of the precipitated solid, and finally immerse the pretreated hemp fiber in the prepared solution at a weight ratio of 1:19, take out after immersion for 5 hours, wash and dry to obtain modified hemp fiber.
[0070] Note: The silane coupling agent used is KH550 silane coupling agent.
[0071] Preparation Example 2
[0072] A modified hemp fiber, which is different from Preparation Example 1 in that it is prepared by the following modification steps:
[0073] S1, taking the hemp fiber raw material at a weight ratio of 1:25 and immersing it in deionized water, and adding 0.8% by weight of silane coupling agent into the deionized water, after immersion treatment for 20 minutes, taking it out and drying it to obtain pretreated hemp fiber;
[0074] S2, take N-acetoacetanilide, propylene glycol and potassium tert-butoxide in a molar ratio of 1:1.1:0.9 in 4 times the mass of DFM solvent, stir and react for 4 hours, pour into saturated sodium chloride solution after the reaction, prepare 8% concentration ethanol solution of the precipitated solid, and finally immerse the pretreated hemp fiber in the prepared solution at a weight ratio of 1:18, take out after immersion for 4 hours, wash and dry to obtain modified hemp fiber.
[0075] Preparation Example 3
[0076] A modified hemp fiber, which is different from Preparation Example 1 in that it is prepared by the following modification steps:
[0077] S1, taking the hemp fiber raw material at a weight ratio of 1:35 and immersing it in deionized water, and adding 1.5% by weight of silane coupling agent into the deionized water, after immersion treatment for 30 minutes, taking it out and drying it to obtain pretreated hemp fiber;
[0078] S2, take N-acetoacetanilide, propylene glycol and potassium tert-butoxide in a molar ratio of 1:1.3:1.1 in 4 times the mass of DFM solvent, stir and react for 4 hours, pour into saturated sodium chloride solution after the reaction, prepare 12% concentration ethanol solution of the precipitated solid, and finally immerse the pretreated hemp fiber in the prepared solution at a weight ratio of 1:20, take out after immersion for 6 hours, wash and dry to obtain modified hemp fiber.
[0079] Preparation Example 4
[0080] A modified cassava starch is prepared by the following modification steps:
[0081] Take cassava starch and deionized water in a ratio of 1g:9ml and mix them. After heating to 92.5°C, add cellulose, keep the temperature for 9 minutes, cool to 37.5°C, add calcium carbonate and polyvinyl alcohol, stir and mix, and finally roll and knead, cut into slices and pellets to obtain modified cassava starch.
[0082] Note: In the above operation, the weight ratio of cassava starch, cellulose, calcium carbonate and polyvinyl alcohol used is 5.5:3.5:2.5:1.
[0083] Preparation Example 5
[0084] A modified cassava starch, which is different from Preparation Example 4 in that it is prepared by the following modification steps:
[0085] Take cassava starch and deionized water in a ratio of 1g:8ml and mix them. After heating to 90°C, add cellulose, keep the temperature for 8 minutes, cool to 35°C, add calcium carbonate and polyvinyl alcohol, stir and mix, and finally roll and knead, cut into slices and pellets to obtain modified cassava starch.
[0086] Preparation Example 6
[0087] A modified cassava starch, which is different from Preparation Example 4 in that it is prepared by the following modification steps:
[0088] Take cassava starch and deionized water in a ratio of 1g:10ml, mix them, heat them to 95°C and then add cellulose, keep the temperature for 10 minutes, cool them to 40°C, add calcium carbonate and polyvinyl alcohol and stir and mix, finally roll and knead them, cut them into pieces and pelletize them to obtain modified cassava starch.
[0089] Preparation Example 7
[0090] A modified cassava starch is different from Preparation Example 4 in that the weight ratio of cassava starch, cellulose, calcium carbonate and polyvinyl alcohol is 4.5:3.5:2:1.
[0091] Preparation Example 8
[0092] A modified cassava starch is different from Preparation Example 4 in that the weight ratio of cassava starch, cellulose, calcium carbonate and polyvinyl alcohol is 6:4:3:1.
[0093] Preparation Example 9
[0094] A modified cassava starch is different from Preparation Example 4 in that the weight ratio of cassava starch, cellulose, calcium carbonate and polyvinyl alcohol is 5.25:4.25:2.5:1. Example
[0095] Example 1
[0096] A degradable lunch box comprises a paper lunch box substrate and a degradable coating disposed on the paper lunch box substrate. The raw materials used to prepare the degradable coating and their corresponding weights are shown in Table 1, and the degradable coating is prepared by the following steps:
[0097] (1) preparing raw materials including polylactic acid, polybutylene succinate, polyglycolic acid, cassava starch, external additives, montmorillonite, boron nitride nanotubes and modified hemp fiber according to a ratio;
[0098] (2) putting the polylactic acid, polybutylene succinate and polyglycolic acid in step (1) into an internal mixer, heating them to a molten state and mixing them evenly, then adding cassava starch and external additives and mixing them for 10 minutes, finally adding montmorillonite, boron nitride nanotubes and modified hemp fibers and mixing them for 20 minutes, and extruding and granulating them to obtain biodegradable coated particles;
[0099] (3) feeding the paper lunch box substrate into a laminating machine, and melting the degradable coating particles and laminating them on the surface of the paper lunch box substrate. The laminating temperature is 150° C., and after cooling, a degradable coating is formed to obtain a coated paper.
[0100] (4) After the coated paper is cut and formed into a box, a degradable lunch box is obtained.
[0101] Note: The modified hemp fiber used was obtained from Preparation Example 1; the particle size of montmorillonite was 75 nm; the diameter of the boron nitride nanotubes was 50 nm, the length was 15 μm, and the specific surface area was 45 m 2 / g; the single fiber fineness of the modified hemp fiber is 22.5μm; the external additive is a composition of filler, thickener and antibacterial and mildew-proof agent in a weight ratio of 8:3:1, the filler is talcum powder, the thickener is hydroxyethyl cellulose, and the antibacterial and mildew-proof agent is polyhexamethylene guanidine hydrochloride.
[0102] Example 2-3
[0103] A degradable lunch box, which is different from Example 1 in that the raw materials used in its preparation and their corresponding weights are shown in Table 1.
[0104]
[0105] Example 4
[0106] A degradable lunch box, which is different from Example 1 in that the particle size of montmorillonite is 50 nm; the diameter of the boron nitride nanotube is 45 nm, the length is 10 μm, and the specific surface area is 40 m 2 / g; the single fiber fineness of the modified hemp fiber is 15μm.
[0107] Example 5
[0108] A degradable lunch box, which is different from Example 1 in that the particle size of montmorillonite is 100 nm; the diameter of the boron nitride nanotube is 55 nm, the length is 20 μm, and the specific surface area is 50 m 2 / g; the single fiber fineness of the modified hemp fiber is 30μm.
[0109] Example 6
[0110] A degradable lunch box is different from Example 1 in that the total amount of montmorillonite, boron nitride nanotubes and modified hemp fiber remains unchanged, and the weight ratio of the three is adjusted to 1.5:0.5:2.
[0111] Example 7
[0112] A degradable lunch box, which is different from Example 1 in that the modified hemp fiber is obtained from Preparation Example 2.
[0113] Example 8
[0114] A degradable lunch box, which is different from Example 1 in that the modified hemp fiber is obtained from Preparation Example 3.
[0115] Example 9
[0116] A degradable lunch box, which is different from Example 1 in that the mass of cassava starch is replaced by modified cassava starch, and the modified cassava starch is obtained by Preparation Example 4.
[0117] Example 10
[0118] A degradable lunch box, which is different from Example 9 in that the modified cassava starch is obtained from Preparation Example 5.
[0119] Embodiment 11
[0120] A degradable lunch box, which is different from Example 9 in that the modified cassava starch is obtained from Preparation Example 6.
[0121] Example 12
[0122] A degradable lunch box, which is different from Example 9 in that the modified cassava starch is obtained from Preparation Example 7.
[0123] Example 13
[0124] A degradable lunch box, which is different from Example 9 in that the modified cassava starch is obtained from Preparation Example 9.
[0125] Embodiment 14
[0126] A degradable lunch box, which is different from Example 9 in that the modified cassava starch is obtained from Preparation Example 9.
[0127] Embodiment 15
[0128] A degradable lunch box, which is different from Example 1 in that the particle size of montmorillonite is 45 nm; the diameter of the boron nitride nanotube is 40 nm, the length is 8 μm, and the specific surface area is 38 m 2 / g; the single fiber fineness of the modified hemp fiber is 13μm.
[0129] Example 16
[0130] A degradable lunch box, which is different from Example 1 in that the particle size of montmorillonite is 1.5 nm; the diameter of the boron nitride nanotube is 60 nm, the length is 22 μm, and the specific surface area is 52 m 2 / g; the single fiber fineness of the modified hemp fiber is 32μm.
[0131] Comparative Example
[0132] Comparative Example 1
[0133] A degradable lunch box, which is different from Example 1 in that montmorillonite and boron nitride nanotubes are not used in the degradable coating.
[0134] Comparative Example 2
[0135] A degradable lunch box, which is different from Example 1 in that montmorillonite and modified hemp fiber are not used in the degradable coating.
[0136] Comparative Example 3
[0137] A degradable lunch box, which is different from Example 1 in that boron nitride nanotubes and modified hemp fibers are not used in the degradable coating.
[0138] Comparative Example 4
[0139] A degradable lunch box, which is different from Example 1 in that montmorillonite is not used in the degradable coating.
[0140] Comparative Example 5
[0141] A degradable lunch box, which is different from Example 1 in that boron nitride nanotubes are not used in the degradable coating.
[0142] Comparative Example 6
[0143] A degradable lunch box, which is different from Example 1 in that no modified hemp fiber is used in the degradable coating.
[0144] Comparative Example 7
[0145] A degradable lunch box, which is different from Example 1 in that montmorillonite, boron nitride nanotubes and modified hemp fibers are not used in the degradable coating.
[0146] Performance testing
[0147] Test samples: The degradable lunch boxes obtained in Examples 1-16 and Comparative Examples 1-7 were used as test samples 1-16 and control samples 1-7, and the thickness of the paper lunch box substrate was 0.35 mm, and the thickness of the degradable coating was 0.08 mm.
[0148] Test method: Take test samples 1-16 and control samples 1-7, use MK-B-90X electric peel strength tester to test the peel strength. The test standard of peel strength should refer to GB / T 8808-1988 "Peel test method for soft composite plastic materials". Each sample is tested three times, and the average value is recorded as A.
[0149] Place the experimental samples 1-16 and the control samples 1-7 in a temperature alternating test chamber, first raise the temperature to 100°C at 5°C / min, then cool it down to 10°C at 2°C / min, continue for 3 cycles, and then naturally return to room temperature for peeling strength test. The test standard of peeling strength should refer to GB / T 8808-1988 "Peeling Test Method for Soft Composite Plastic Materials". Each sample is tested three times, and the average value is recorded as B;
[0150] The peel strength loss rate was calculated for each sample, peel strength loss rate (%) = (AB) / A, and then recorded in Table 2 for the test samples 1-16 and the control samples 1-7.
[0151]
[0152]
[0153] It can be seen from Examples 1-3 and Comparative Examples 1-7 and Table 2 that the compound use of montmorillonite, boron nitride nanotubes and modified hemp fibers in the degradable coating can make the degradable coating exhibit strong resistance to temperature changes, maintain relatively stable adhesion with the paper lunch box substrate, and is not prone to large peel strength loss. The peel strength loss rate obtained by the test is also relatively small; at the same time, if only any one or two of montmorillonite, boron nitride nanotubes and modified hemp fibers are used in the degradable coating, the improvement in the temperature change resistance of the degradable coating is very limited, and the combination of any two can only bring about a simple superposition of the improvement effect, and only when the three are used together can a significant improvement effect of 1+1>2 be brought.
[0154] Combining Example 1 with Example 4-5 and Table 2, it can be seen that the particle size of montmorillonite is 50-100 nm; the diameter of the boron nitride nanotube is 45-55 nm, the length is 10-20 μm, and the specific surface area is 40-50 m 2 / g; the single fiber fineness of the modified hemp fiber is 15-30μm; all of them can ensure that montmorillonite, boron nitride nanotubes and modified hemp fibers are stably matched and exert excellent corresponding effects, so that the combination of the degradable coating and the paper lunch box substrate shows excellent temperature change resistance. Combined with Examples 15-16 and Table 2, it can be seen that if montmorillonite, boron nitride nanotubes and modified hemp fibers exceed the above specification range, it is found that the peel strength loss rate obtained by the test will increase significantly.
[0155] In combination with Example 1 and Examples 9-11 and Table 2, it can be seen that the present application uses a combination of cellulose, calcium carbonate and polyvinyl alcohol to modify cassava starch, which can further improve the bonding stability between the degradable coating and the paper lunch box substrate, so that the temperature change resistance of the degradable lunch box is further improved; in combination with Examples 12-14 and Table 2, it can be seen that in the preparation of modified cassava starch, when the weight ratio of cassava starch, cellulose, calcium carbonate and polyvinyl alcohol is 5.5:3.5:2.5:1, the improvement of the temperature change resistance of the degradable lunch box can play a better improvement effect, and the measured peel strength loss rate is also relatively small.
[0156] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A degradable lunch box, characterized in that: It comprises a paper lunch box substrate and a degradable coating disposed on the paper lunch box substrate, wherein the degradable coating is made of the following raw materials in parts by weight: Polylactic acid 40-50 parts; 10-15 parts of polybutylene succinate; Polyglycolic acid 15-20 parts; 10-20 parts of tapioca starch; 5-8 parts of external additives; Montmorillonite 1.2-1.8 parts; Boron nitride nanotubes 0.2-0.8 parts; 1.5-2.5 parts of modified hemp fiber; The modified hemp fiber is prepared by the following modification steps: S1, taking the hemp fiber raw material at a weight ratio of 1: (25-35) and immersing it in deionized water, and adding 0.8-1.5% by weight of silane coupling agent into the deionized water, immersing for 20-30 minutes, taking it out and drying it to obtain pretreated hemp fiber; S2, taking N-acetoacetanilide, malonic acid dicyandiamide and potassium tert-butoxide in a molar ratio of 1: (1.1-1.3): (0.9-1.1) and stirring the mixture in a DFM solvent, and after the reaction, pouring the mixture into a saturated sodium chloride solution, preparing the precipitated solid into an 8-12% ethanol solution, and finally immersing the pretreated hemp fiber in the prepared solution at a weight ratio of 1: (18-20), taking it out after immersion for 4-6 hours, washing it with water and drying it to obtain a modified hemp fiber; The external additive is a composition of filler, thickener and antibacterial and antifungal agent in a weight ratio of 8:3:1, the filler is talcum powder, the thickener is hydroxyethyl cellulose, and the antibacterial and antifungal agent is polyhexamethylene guanidine hydrochloride.
2. The degradable lunch box according to claim 1, characterized in that: The weight ratio of the montmorillonite, the boron nitride nanotubes and the modified hemp fiber is 1.5:0.5:
2.
3. The degradable lunch box according to claim 1, characterized in that: The particle size of the montmorillonite is 50-100nm; the diameter of the boron nitride nanotube is 45-55nm, the length is 10-20μm, and the specific surface area is 40-50m 2 / g; the single fiber fineness of the modified hemp fiber is 15-30μm.
4. The degradable lunch box according to claim 1, characterized in that: The cassava starch is modified before use, and the modification steps are as follows: Take cassava starch and deionized water in a ratio of 1g: (8-10) ml, mix them, heat them to 90-95°C, add cellulose, keep them at a constant temperature for 8-10 minutes, cool them to 35-40°C, add calcium carbonate and polyvinyl alcohol, stir and mix, and finally roll and knead them, then cut them into pieces and pelletize them to obtain modified cassava starch; In the above modification treatment, the weight ratio of cassava starch, cellulose, calcium carbonate and polyvinyl alcohol is (4.5-6): (3.5-4): (2-3):
1.
5. The degradable lunch box according to claim 4, characterized in that: The weight ratio of the cassava starch, cellulose, calcium carbonate and polyvinyl alcohol is 5.5:3.5:2.5:
1.
6. The degradable lunch box according to claim 1, characterized in that: The external additive is one or a combination of fillers, thickeners and antibacterial and antifungal agents.
7. The degradable lunch box according to claim 6, characterized in that: The filler is one or a combination of talcum powder, silica powder, mica powder, silicon whisker, calcium whisker, glass fiber, titanium dioxide and glass microbeads.
8. The degradable lunch box according to claim 6, characterized in that: The thickener is one or a combination of sodium carboxymethyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl cellulose, sodium alginate and polyacrylamide.
9. The degradable lunch box according to claim 6, characterized in that: The antibacterial and antifungal agent is polyhexamethyleneguanidine hydrochloride.
10. The method for preparing a degradable lunch box according to claim 1, characterized in that: The following steps are involved: (1) preparing raw materials including polylactic acid, polybutylene succinate, polyglycolic acid, cassava starch, external additives, montmorillonite, boron nitride nanotubes and modified hemp fiber according to a ratio; (2) heating the polylactic acid, polybutylene succinate and polyglycolic acid in step (1) to a molten state and mixing them uniformly, then adding cassava starch and external additives and mixing them, and finally adding montmorillonite, boron nitride nanotubes and modified hemp fibers and mixing them, and extruding and granulating them to obtain biodegradable coated particles; (3) feeding the paper lunch box substrate into a laminating machine, and melting the degradable coating particles and laminating them on the surface of the paper lunch box substrate, and forming a degradable coating after cooling to obtain a coated paper; (4) After the coated paper is cut and formed into a box, a degradable lunch box is obtained.
Citation Information
Patent Citations
Full biodegradable fiber-reinforced starch foaming tableware and preparation method thereof
CN106947117A
Coating for material surface treatment, coating layer thereof, and preparation method of coating layer
CN109957262A